Dual‐Graphene Rechargeable Sodium Battery. Issue 47 (27th October 2017) - Wang, Faxing; Liu, Zaichun; Zhang, Panpan; Li, Hongyan; Sheng, Wenbo; Zhang, Tao; Jordan, Rainer; Wu, Yuping; Zhuang, Xiaodong; Feng, Xinliang
Abstract: Sodium (Na) ion batteries are attracting increasing attention for use in various electrical applications. However, the electrochemical behaviors, particularly the working voltages, of Na ion batteries are substantially lower than those of lithium (Li) ion batteries. Worse, the state‐of‐the‐art Na ion battery cannot meet the demand of miniaturized in modern electronics. Here, we demonstrate that electrochemically exfoliated graphene (EG) nanosheets can reversibly store (PF6 − ) anions, yielding high charging and discharging voltages of 4.7 and 4.3 V vs. Na + /Na, respectively. The dual‐graphene rechargeable Na battery fabricated using EG as both the positive and negative electrodes provided the highest operating voltage among all Na ion full cells reported to date, together with a maximum energy density of 250 Wh kg −1 . Notably, the dual‐graphene rechargeable Na microbattery exhibited an areal capacity of 35 μAh cm −2 with stable cycling behavior. This study offers an efficient option for the development of novel rechargeable microbatteries with ultra‐high operating voltage and high energy density. Abstract : A dual‐graphene rechargeable Na microbattery fabricated using electrochemically exfoliated graphene as both the positive and negative electrodes provides a high operating voltage together with stable cycling behavior.